Ethephon-induced changes in antioxidants and phenolic compounds in anthocyanin-producing black carrot hairy root cultures. (17th August 2020) - Barba-Espín, Gregorio; Chen, Shih-Ti; Agnolet, Sara; Hegelund, Josefine Nymark; Stanstrup, Jan; Christensen, Jan H; Müller, Renate; Lütken, Henrik
Abstract: Hairy root (HR) cultures are quickly evolving as a fundamental research tool and as a bio-based production system for secondary metabolites. In this study, an efficient protocol for establishment and elicitation of anthocyanin-producing HR cultures from black carrot was established. Taproot and hypocotyl explants of four carrot cultivars were transformed using wild-type Rhizobium rhizogenes . HR growth performance on plates was monitored to identify three fast-growing HR lines, two originating from root explants (lines NB-R and 43-R) and one from a hypocotyl explant (line 43-H). The HR biomass accumulated 25- to 30-fold in liquid media over a 4 week period. Nine anthocyanins and 24 hydroxycinnamic acid derivatives were identified and monitored using UPLC-PDA-TOF during HR growth. Adding ethephon, an ethylene-releasing compound, to the HR culture substantially increased the anthocyanin content by up to 82% in line 43-R and hydroxycinnamic acid concentrations by >20% in line NB-R. Moreover, the activities of superoxide dismutase and glutathione S -transferase increased in the HRs in response to ethephon, which could be related to the functionality and compartmentalization of anthocyanins. These findings present black carrot HR cultures as a platform for the in vitro production of anthocyanins and antioxidants, and provide new insight into the regulation of secondary metabolism in black carrot. Abstract : Fast-growing black carrot hairy roots accumulate anthocyanins. The elicitor ethephon enhances the anthocyanin content, alters the composition of phenolics, and increases the antioxidant production in hairy root cultures.